2018
DOI: 10.3892/ol.2018.8719
|View full text |Cite
|
Sign up to set email alerts
|

Absent expression of miR‑30a promotes the growth of lung cancer cells by targeting MEF2D

Abstract: Abstract. The microRNA (miR)-30 family has been reported to be aberrantly expressed in several types of cancer. However, its contributions to lung cancer remain to be fully elucidated. Myocyte enhancer factor 2D (MEF2D), an oncogene in liver cancer, has been shown to be aberrantly expressed in lung cancer. In the present study, it was found that MEF2D and miR-30a were inversely correlated in lung cancer samples. Using an online database, it was predicted that miR-30a targeted the 3' untranslated region (UTR) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
(29 reference statements)
1
13
0
Order By: Relevance
“…In addition, further experiments that shed light on XB130 protein expression in cancer and paracancerous tissues and perform correlations of the expression levels of the miR-30 family and XB130 in cancer tissues from patients with NSCLC are required to verify the findings of the present study. Combined with the low expression levels of miR-30 family members exhibited by patients with NSCLC ( 7 , 11 14 ), the present results supported the hypothesis that enhancing miR-30 family expression levels or silencing XB130 may provide improved survival benefit for patients with NSCLC ( 13 , 31 , 36 39 ).…”
Section: Discussionsupporting
confidence: 83%
“…In addition, further experiments that shed light on XB130 protein expression in cancer and paracancerous tissues and perform correlations of the expression levels of the miR-30 family and XB130 in cancer tissues from patients with NSCLC are required to verify the findings of the present study. Combined with the low expression levels of miR-30 family members exhibited by patients with NSCLC ( 7 , 11 14 ), the present results supported the hypothesis that enhancing miR-30 family expression levels or silencing XB130 may provide improved survival benefit for patients with NSCLC ( 13 , 31 , 36 39 ).…”
Section: Discussionsupporting
confidence: 83%
“…In vitro experiments indicated that miR-30d could attenuate the proliferation and viability of NSCLC cells [ 141 ]. The aberrant expression of miR-30a in lung cancer stimulated the expression of myocyte enhancer factor 2D (MEF2D) protein [ 142 ]. The myocyte enhancer factor 2 (MEF2) family of human transcription factors, consisting of four subtypes, MEF2-A, -B, -C, and -D, has a diversity of functions in different tissues and has been implicated in numerous diseases.…”
Section: Asbestos and Micrornamentioning
confidence: 99%
“…In NSCLC tissues, miR-30a expression was significantly down-regulated, while Snail expression was up-regulated considerably, which can decrease E-cadherin and occludin expression, and promote N-cadherin and vimentin expression to induce apoptosis [32]. MiR-30a overexpression can also inhibit MEF2D and GRP78, reduce apoptosis, and promote the growth of lung cancer and cell renal cell carcinoma (ccRCC) cells, respectively [33,34]. Besides, miR-30c was involved in the regulation of cisplatin-induced apoptosis in renal tubular cells by targeting the BNIP3L and Hspa5 [35].…”
Section: Mechanism Of Action Of the Mir-30 Familymentioning
confidence: 99%